2004
DOI: 10.3989/scimar.2004.68s3153
|View full text |Cite
|
Sign up to set email alerts
|

Chondrichthyes species in deep waters of the Mediterranean Sea

Abstract: SUMMARY: Data collected during the DESEAS survey carried out in three areas of the Mediterranean Sea (Balearic Sea, western and eastern Ionian Sea) were used to describe the distribution and abundance of chondrichthyes species at depths between 600 and 4000 m. A total of 8 chondrichthyes species were recorded, 5 of them in the Balearic Sea, 4 in the western Ionian and 6 in the eastern Ionian. A decrease in abundance with depth was observed in each species with the exception of Centroscymnus coelolepis. The mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 21 publications
5
65
0
Order By: Relevance
“…[31]); however, it can reach a depth up to 800 m (in Ref. [44]). The maximum TL recorded was 150 cm (in Ref.…”
Section: Angular Roughshark-oxynotus Centrina Linnaeus 1758mentioning
confidence: 99%
See 1 more Smart Citation
“…[31]); however, it can reach a depth up to 800 m (in Ref. [44]). The maximum TL recorded was 150 cm (in Ref.…”
Section: Angular Roughshark-oxynotus Centrina Linnaeus 1758mentioning
confidence: 99%
“…In the Mediterranean, C. monstrosa is usually caught by offshore trawlers mostly between 500 and 800 m (in Refs. [32,44]) and immediately discarded (in Ref. [8]).…”
Section: Rabbitfish-chimaera Monstrosa Linnaeus 1758mentioning
confidence: 99%
“…During the DESEAS cruise in the Mediterranean (financed by the EC), it was caught at depths of 1500, 2500 and 2800 m (cf. Sion et al, 2004). As sharks occupy a high level in the marine trophic chain, identifying the special role of their sensory organs is one of the means of understanding their behavioural response.…”
Section: Introductionmentioning
confidence: 99%
“…O. centrina is a sluggish shark found over the continental shelf and upper slope at depth ranges generally between 60 and 660 m (COMPAGNO, 1984); however, a recent DESEAS survey revealed that lower limit of the depth range of the angular rough shark extends to 800 m in the western Ionian Sea (SION et al, 2004), and the upper limit may cover shallower areas around 30 m, as observed in the present study.…”
Section: Introductionmentioning
confidence: 44%
“…The rarity of O. centrina in the Turkish waters has become obvious after the most recent thorough investigations. O. centrina is considered to be a deepwater shark (COMPAGNO, 1984;SION et al, 2004); however, the present study has shown that it can ascend to shallower depths of around 30 m. Nocturnal excursions to shallow water by the angular rough shark increase the chance of incidental captures by coastal fishing gear, coastal gill-netting in particular. Furthermore, the shallower the angular rough shark occurs, the higher the chance of encountering divers.…”
Section: Discussionmentioning
confidence: 67%